The Effect of Promotion, Brand Image, and Service Quality on Purchasing Decisions for Garuda Indonesia Airline Tickets - Ade Ray Hidayat; Hery Pudjoprastyono (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze and find out whether promotion, brand image, and service quality influence the decision to purchase Garuda Indonesia airline tickets. The approach used in this study is an approach with quantitative methods. The type of research used in this research is descriptive research. This study used the interview method using primary data obtained by distributing questionnaires as a data collection technique. The population used in this study is all consumers who have flown using the Garuda Indonesia airline. The sampling technique used in this study was a purposive sampling technique. A total of 80 respondents were taken as samples of this study based on Ferdinand's theory (2002, 48). The analysis technique in this study uses the Partial Least Square (PLS) analysis technique. The results of this study indicate that promotion (X1), brand image (X2), and service quality (X3) have a significantly positive effect on purchasing decisions (Y). This means that if variable (X) is increased, there will also be an increase in purchasing decisions (Y).